Against autonomy : justifying coercive paternalism - Conly, Sarah (Cambridge : Cambridge University Press, 2013)
'Since Mill's seminal work On Liberty, philosophers and political theorists have accepted that we should respect the decisions of individual agents when those decisions affect no one other than themselves. Indeed, to respect autonomy is often understood to be the chief way to bear witness to the intrinsic value of persons. In this book, Sarah Conly rejects the idea of autonomy as inviolable. Drawing on sources from behavioural economics and social psychology, she argues that we are so often irrational in making our decisions that our autonomous choices often undercut the achievement of our own goals. Thus in many cases it would advance our goals more effectively if government were to prevent us from acting in accordance with our decisions. Her argument challenges widely held views of moral agency, democratic values and the public/private distinction, and will interest readers in ethics, political philosophy, political theory and philosophy of law'--
Includes bibliographical references (pages 195-203) and index.
Keywords: Decision making -- Political aspects; Decision making -- Philosophy; Paternalism; Autonomy (Philosophy); Choice (Psychology)